Simulation-Based Selection of Transmitting Antenna Type for Enhanced Loran System in Selected Location - Zhaopeng Hu; Ming Dong; Shifeng Li; Chanzhong Yang (Applied Sciences, 2022)
To improve the coverage and timing capability of enhanced Loran signals, three enhanced Loran transmitters are planned to be built in Western China. The most appropriate antenna configuration can be determined by comparing domestic and foreign mainstream small and radio antennas. By analyzing and comparing the electrical and structural parameters and signal propagation curves of the transmitting antenna, it can be concluded that the single tower umbrella antenna provides the best performance in all evaluation indexes, and the enhanced Loran signal can be transmitted to areas 1000 km away through the single tower umbrella antenna so that the enhanced Loran signal covers most areas of Western China. Therefore, it should be widely used in the construction of enhanced Loran transmitters in the future.